The Results of Echocardiography Applied to Heart Murmurs in Two Different Centers: is Geography Destiny? - Aydemir, Merve Maze; Yukcu, Bekir; Tahiroglu, Veysel (Istanbul Univ, 2024)
Objective: Heart murmurs in childhood are the most common reason for pediatric cardiology consultations worldwide. The aim of this study is to investigate the frequency and etiology of congenital heart disease (CHD) in two different centers possessing significant differences in factors such as geography, climate, and sociocultural conditions. Methods: The study involves patients who'd been referred to the pediatric cardiology outpatient clinic due to heart murmurs between November 2022-October 2023. All patients were evaluated by echocardiograph to investigate the causes of the murmur. Results: The study includes 2,127 patients (1,452 from S & imath;rnak and 675 from Giresun; median age = 1.95 years). The gender distributions were similar in both regions. Pathological heart murmurs were more prevalent in S & imath;rnak (21.6%) compared to Giresun (7.7%), while Giresun had a higher percentage of innocent murmurs (92.3%). Cyanotic conditions were rare. Surgery was required for 3.7% of patients overall (4.5% in S & imath;rnak; 1.9% in Giresun). Normal echocardiograms were found in 46% of the total population, with variations being 41% in S & imath;rnak and 56% in Giresun. Pathological murmurs were more common in females. Patients with pathological murmurs were more likely to require surgery. S & imath;rnak had more pathological echocardiography results and a higher need for surgery. Neonates were the age group most frequently requiring surgery in both centers. Conclusions: Educating society and fostering awareness are imperative steps for preventing consanguineous marriages and encouraging appropriate birth intervals. Swift public education is particularly crucial in developing nations marked by elevated consanguinity rates and limited financial resources, highlighting the potential detrimental consequences of inbreeding.
Keywords: Child; echocardiography; cardiac murmur